P73 is required for ependymal cell maturation and neurogenic SVZ cytoarchitecture. Issue 7 (31st October 2015) - Gonzalez‐Cano, L.; Fuertes‐Alvarez, S.; Robledinos‐Anton, N.; Bizy, A.; Villena‐Cortes, A.; Fariñas, I.; Marques, M.M.; Marin, Maria C.
ABSTRACT: The adult subventricular zone (SVZ) is a highly organized microenvironment established during the first postnatal days when radial glia cells begin to transform into type B‐cells and ependymal cells, all of which will form regenerative units, pinwheels, along the lateral wall of the lateral ventricle. Here, we identify p73, a p53 homologue, as a critical factor controlling both cell‐type specification and structural organization of the developing mouse SVZ. We describe that p73 deficiency halts the transition of the radial glia into ependymal cells, leading to the emergence of immature cells with abnormal identities in the ventricle and resulting in loss of the ventricular integrity. p73‐deficient ependymal cells have noticeably impaired ciliogenesis and they fail to organize into pinwheels, disrupting SVZ niche structure and function. Therefore, p73 is essential for appropriate ependymal cell maturation and the establishment of the neurogenic niche architecture. Accordingly, lack of p73 results in impaired neurogenesis. Moreover, p73 is required for translational planar cell polarity establishment, since p73 deficiency results in profound defects in cilia organization in individual cells and in intercellular patch orientation. Thus, our data reveal a completely new function of p73, independent of p53, in the neurogenic architecture of the SVZ of rodent brain and in the establishment of ependymal planar cell polarity with important implications in neurogenesis. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 730–747, 2016